Skyscraper gothic : medieval style and modernist buildings - Reilly, Lisa A.; Reilly, Lisa A.; Murphy, Kevin D.; Murphy, Kevin D. (University of Virginia Press, 2017)
Introduction: skyscraper gothic from nineteenth-century to postmodern expressions -- Design and the study of the past: the gothic skyscraper / Lisa Reilly -- The gothics of Francis Kimball: from nineteenth-century revivals to the early skyscraper / Kevin D. Murphy -- Medievalism, mysticism, and modernity in early twentieth-century New York: Cass Gilbert's "skyscraper gothic" / Gail Fenske -- The gothics revival and the Chicago school: from naturalistic ornament to constructive expression / Joanna Merwood-Salisbury -- Tribune tower : medievalism and memory in the wake of the Great War / Katherine M. Solomonson -- Forward Atlanta: G. Lloyd preacher and the Atlantic City Hall / Carrie Albee -- Gothic with an American accent: the cathedral of learning / Anke Koeth -- Radiant heat and glowing lights: Raymond Hood's American radiator building / Christine G. O'Malley.